Experimental Study on concrete behaviour with Partial Replacement of M-Sand with Unexpanded Perlite - Premalatha P.V.; Geethanjali M.; Rahuraman T.; Gurusaran S. (E3S Web of Conferences, 2023)
Traditionally, river sand was utilized as fine aggregate in concrete manufacturing. However, due to the ongoing extraction of natural river sand, its availability has become limited. Construction businesses have begun to explore for alternative sustainable resources to use as fine aggregate. Manufactured sand (M- sand), recycled concrete aggregate, crushed granite, rice husk ash, fly ash, and other materials can cause dumpsite and environmental contamination. These materials are viable substitutes for natural river sand as fine aggregate. Unexpanded perlite is also one such material which can be used as a replacement for fine aggregate. Unexpanded Perlite is a natural material in the form of volcanic glass resulted from cooled lava. This paper presents the utilization of M-Sand with partial replacement of unexpanded perlite as a fine aggregate. In the present research, the effect of unexpanded Perlite with M- sand in concrete is studied to determine the mechanical properties such as compressive strength at 7 days, 14 days and 28 days, split tensile strength at 28days and flexural strength at 28 days. M-Sand is used in the range of 62%, 60%, 58%, 56%, 54%, 52% and 50% with Unexpanded Perlite UP in the percentage of 38%, 40%, 42%, 44%, 46%, 48% and 50% respectively. The Unexpanded Perlite can withstand the 1.5 times of thermal resistivity when compared to the conventional concrete.